TENTANG KONSEP KEBUDAYAAN - Kistanto, Nurdien Harry (Sabda: Jurnal Kajian Kebudayaan, 2015)
Human consciousness towards the experience encouraged him composing formulation, definitions, and theories about the ways of his life, into the conception about culture. Consciousness thus commenced from the gift of reason, his human instincts and feelings, which are not owned by other beings, such as animals. Leslie White (1973), defined the conception of culture that includes "beliefs, ideologies, social organization, and technology (the use of tools)." In the second half of the 19th century Sir Edward Burnett Tylor, conducted a study of "primitive societies," which functions as the foundation for putting together the concept of culture: "Culture or Civilization ... is that complex which includes knowledge, belief, art, morals, law, custom, and many other capabilities and habits acquired by man as a member of society.â€ Three quarters of a century later, Ralph Linton (1945), offers a formula about the culture that emphasized on the factor of integration achieved through a learning behavior: "A culture is the configuration of learned behavior and results of behavior whose component elements are shared and transmitted by the members of a particular society." While according to Koentjaraningrat (1974), elements of culture include (1) social organization systems; (2) systems of religion and religious ceremonies; (3) livelihood systems; (4) science and knowledge systems; (5) technology and equipment systems; (6) language systems; and (7) arts. Meanwhile, Anthony Giddens (1991), conceptualized culture by referring to the whole way of life of the members of a society. With the concepts of culture, background and multi-cultural experiences, in the communities of nation of Indonesia there can be arranged Indonesian socio-cultural systems.